2014
DOI: 10.1504/ijex.2014.065707
|View full text |Cite
|
Sign up to set email alerts
|

Exergy analysis and optimisation of collector dimensions in a solar chimney power plant using entropy generation minimisation method

Abstract: The purpose of this study is to optimise the dimensions of the collector in a solar chimney power plant with entropy generation minimisation (EGM) method. Projection method, based on second-order finite difference discretisation, is developed to solve the coupled equations of continuity, momentum and energy of laminar natural convection in a fully staggered grid. Numerical solution showed that the irreversibility owing to heat transfer is dominant in solar collector and the chimney has minor role in total entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A wind turbine is always situated where the updraft velocity in Equation (7), which is where it achieves its highest value at solar towers base region. There are various factors listed as 1) Solar tower height 2) Gravity 3) Temperature of air flow rate 4) Ambient conditions and 5) updraft velocity.…”
Section: Fig 2 Solar Chimney -Divergent Designmentioning
confidence: 99%
“…A wind turbine is always situated where the updraft velocity in Equation (7), which is where it achieves its highest value at solar towers base region. There are various factors listed as 1) Solar tower height 2) Gravity 3) Temperature of air flow rate 4) Ambient conditions and 5) updraft velocity.…”
Section: Fig 2 Solar Chimney -Divergent Designmentioning
confidence: 99%
“…C. Lou and Z. Zhang [12] conducted a decoupled analysis of radiative heat transfer in a coal-fired boiler based on its entropy generation characteristics. K. Pitchandi et al [13] and A. Arefian et al [14] performed parameter optimization studies of collectors and heat exchangers using the EGA method, respectively. In our previous study, we analyzed the influence of billet charging temperature and fuel mass flow rate on the entropy generation and exergy efficiency of a regenerative reheating furnace based on a heating unit model [15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the overall dimension of the collector is one of the important parameters to determine the power generation efficiency of the system [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%